Loss of effort in chronic low-back pain patients: Motivational anhedonia in chronic pain - Samuel Alldritt; Mohammad Jammoul; Meena Makary; Susanne Becker; Daniel Maeng; Brian Keane; David Zald; Paul Geha (PLoS ONE, 2025)
The motivational and affective properties of chronic pain significantly impact patients’ lives and response to treatment but remain poorly understood. Most available phenotyping tools of chronic pain affect rely on patients’ self-report. Here we instead directly studied the willingness of chronic low-back pain (CLBP, n = 82) patients to expend effort to win monetary rewards available for wins at different probabilities and different levels of difficulties in comparison to matched pain free controls (n = 43). Consistent with the hypothesis of “negative hedonic shift” in chronic pain we observed that CLBP patients are significantly less willing than pain free controls to expend effort to go for high cost/high reward choices and their reported low-back pain intensity predicted increased effort discounting. Patients’ performance was not explained by their self-reported depressive symptoms. Our results present new behavioral evidence characterizing the nature of anhedonia in chronic pain and highlight the importance of recognizing and assessing diminished motivation as an integral component of the chronic pain experience.